Investigation of stability, dynamics and scope of application of mycobacterial porin MspA: a highly versatile biomolecular resource - Perera, Jayaweeralage Ayomi Sheamilka (Kansas State University, 2012)
Porin A from Mycobacterial smegmatis (MspA) is an octameric trans-membrane channel protein and is one of the most stable porins known to date. MspA has been successfully isolated and purified to obtain liquid extracts and crystals using a modified extraction procedure. A full analytical assessment has been carried out to authenticate its’ structure, including gel electrophoresis, spectroscopy (fluorescence, UV, FTIR, NMR), HPLC, Bradford protein assay, dynamic light scattering and X-ray crystallography. Nanoscopic vesicle formation of MspA molecules in aqueous media has been thoughroughly investigated. Temperature dependent dynamic light scattering experiments reveal that size of such vesicles is dependent on temperature but is independent of ionic strength of the medium. Zeta potential measurements reveal a steady build up of positive charge on the vesicle surface with increasing temperature. For the first time, wild type (WT) MspA has been utilized as a channel forming agent. This phenomenon has future potential in DNA sequencing and the development of antimycobacterial drugs. Channel activity of WT MspA and mutant A96C MspA has been investigated and has shown to form stable channels across DPhPC lipid bilayers. Blocking of the channel current via external molecules (i.e. channel blocking) is an extremely important process, which helps to evaluate the biosensor ability of the pore. In this regard, two Ruthenium based compounds, Ru(QP-C2)38+ (i.e. RuC2) and Ru(bpy)32+have been successfully employed as channel blocking agents. Both compounds show evidence for channel blocking of WT MspA. However, these results are not reproducible. Three dimensional aggregation behavior of RuC2-MspA vesicles have been thoughroughly investigated. It is evident that addition of RuC2 significantly increases vesicle size and polydispersity of MspA aggregates in solution. The results provide explanations onto the lack of channel blocking ability of MspA by RuC2. Development of a ‘greener’ dye sensitized solar cell with the use of MspA as an electron carrier is investigated for the first time. A series of Ru(II)-phenanthroline-based dyes have been synthesized as non-toxic dyes in this regard. Chemical binding between the dyes and MspA has been achieved successfully. Two types of solar cell prototypes, i.e. TiO2-based (Grätzel type) and FTO-based have been developed and tested. Significant current generation and conversion efficiencies have been achieved for both cell types. This marks the first development of a protein-based photovoltaic device, which has the potential to be developed as a new class of “hybrid soft solar cells”.
Keywords: Mycobacterium smegmatis; MspA; Protein solar cell; Alternative Energy (0363); Biochemistry (0487); Chemistry (0485)